(untitled) (Comprehensive Journal of Science, 2026)
This study aimed primarily to examine the extent to which the accounting education program at the Accounting Department, Faculty of Economics, Al-Kufra University, aligns with the requirements of International Accounting Standard 2 (IAS 2). It also sought to familiarize participants with accounting education and the International Accounting Standards issued by the International Federation of Accountants (IFAC). The study employed a descriptive methodology, collecting data from available documents within the Accounting Department at the Faculty of Economics. Data analysis was conducted using content analysis. The study found a relative alignment of 72.3% between the knowledge presented in the accounting education program at Al-Kufra University and the knowledge stipulated in IAS 2. Specifically, the study found that the alignment percentages for each piece of knowledge presented in the accounting program at Al-Kufra University and the knowledge required by IAS 2 ranged from 0% to 100%. The accounting program at Al-Kufra University largely complies with most of the requirements of International Accounting Standard 2 (IAS 2), but not with two areas of knowledge: governance, risk management, and internal control, and information and communication technology (ICT) knowledge. Therefore, the study recommends updating the accounting education program and adopting a curriculum specifically for governance, risk management, and internal control. It also recommends developing the computer science curriculum to include ICT knowledge in accordance with IAS 2. Furthermore, the study emphasizes the importance for accounting program specialists to prioritize the study and application of IAS 2 in educational institutions to ensure high-quality educational programs that keep pace with developments in the modern business environment. Finally, the study stresses the need for educational institutions and organizations to study and apply IAS 2 and develop their educational programs based on IAS requirements. This will facilitate graduates’ ability to pursue advanced educational programs internationally and stay abreast of modern developments.